Leading the localities : Executive mayors in English local governance. - Copus, Colin (Manchester University Press, 2006)
This book is the result of national research conducted amongst England?s directly elected mayors and the councillors that serve alongside them. It is the first such major publication to assess the impact on local politics of this new office and fills a gap in our understanding of how the Local Government Act 2000 has influenced local governance. The book also draws from a range of research that has focused on elected mayors - in England and overseas - to set out how the powers, roles and responsibilities of mayors and mayoral councils would need to change if English local politics is to fundam.